Cost of care and impact on quality of life of upper urinary tract infections in South India with a focus on diabetics and extended-spectrum beta-lactam producing organisms - Ebenezer Daniel; Bijesh Yadav; Lakshmanan Jeyaseelan; Malavika Babu; Selvin Sundar Raj Mani; Alice Joan Mathuram; Sowmya Sathyendra; Samuel George Hansdak; Ramya Iyyadurai; Rani Diana Sahni; Thambu David Sudarsanam (Wolters Kluwer Medknow Publications, 2022)
Background and Objectives: Upper urinary tract infections (UTIs) that require in-patient care can be expensive. Comorbid conditions such as diabetes as well as UTI due to extended-spectrum beta-lactamase (ESBL) producing bacteria may affect costs. The quality of life of patients with this condition has not been described. Methods: This was a cost of illness study that prospectively evaluated patients admitted with upper UTI to a medical ward in a tertiary care hospital. Direct medical and nonmedical costs, indirect costs were collected to make the total cost per admission. Quality of life was assessed using the World Health Organization Quality of Life-BREF score. We also compared costs between those with and without diabetes or ESBL infection. Results: Between March 2016 and July 2017, 92 eligible patients were included in the study. The average age was 55.8 years; two thirds were diabetics. The mean overall cost of a single admission for upper UTI was INR.88, 330.2 (1370.4 USD). This was INR.96, 193.0 (1492.6 USD) and INR.1, 03,154.9 (1600.4 USD) among those with diabetes mellitus and ESBL infection, respectively. The cost was higher among those with diabetes and ESBL than those without; this difference reached statistically significance for the ESBL group. The quality of life was affected in all domains; the psychological being most affected among diabetics and ESBL infected. Conclusions: The mean total cost of admission for an upper UTI in a tertiary care hospital in South India was INR 88,330 (1370.4 USD). This is higher if the patient has diabetes or ESBL organism causing the UTI. Quality of life is clearly reduced especially in the psychological domain.